Optimal Acupuncture Therapeutic Projects for Cerebral Infarction-related Motor Dysfunction of Lower Limbs - 范刚启 赵扬 沈卫平 曹树平 吕莉君 韩丑萍（Translator） (Journal of acupuncture and tuina science, 2007)
Objectiveto select the optimal acupuncture therapeutic projects on cerebral infarction-related motor dysfunction of lower limbs.Methodsto optimize the combination projects on 4 factors and 3 levels affecting the acupuncture effect on cerebral infarction by using orthogonal design targeting on patients with cerebral infarction-related motor dysfunction of lower limbs, and Fugl-Meyer score of limb motor function was taken as indexes.ResultsThe relatively optimal Fugl-Meyer score of lower limb function can be obtained within 3-day duration of cerebral infarction.ConclusionsAs far as the considered factors and levels are concerned, the previously mentioned project is the optimal acupuncture therapeutic project for cerebral infarction-related motor dysfunction of lower limbs.